Egizi e cittadinanza romana - Marotta, Valerio (Cultura giuridica e diritto vivente, 2014)
[Egyptians and roman citizenship] In the 1st century AD, the Egyptians, in contrast to the vast majority of the peregrini who inhabited the other provinces of the Empire, were only admitted in exceptional cases to Alexandrian or Roman citizenship (see Plin. Epp. 10.5, 10.6, 10.7, 10.10, Josephus’ Contra Apionem 2.40-41 [but cf. also 2.28-30 e 2.72] and the § 55 of the Gnōmōn of the Ídios Lógos). After Hadrian the Egyptian institutional pattern underwent a deep change. Between the 2nd and the 3rd century its institutions conformed to those of the other provinces. In 200 AD the administrative structure of the Egyptian metropoleis changed fundamentally when Severus ordered the creation of a boulé, or town council, in the capital of each name. It is therefore likely that in 212 AD the Egyptians as well benefited from the «divine gift». Yet neither the restrictions concerning their status nor the social structure of Egypt underwent essential changes.